Factors that drive employee job satisfaction and its overall influence on the intention to leave in a startup - Vo, Thu (My University, 2021)
Despite employees being reported to be more satisfied in a small workplace, startup companies are still facing many challenges regarding hiring and retaining good employees. Knowing that the employees are becoming more important to the company’s competitive advantages especially for those who rely on innovation, understanding employee job satisfaction and their intention to leave is essential. Although the study of the relationship between job satisfaction and turnover intention is not new to the field, there is a shortage of focus on this subject in a small working environment. The research aims to examine the influence factors of job satisfaction from the employee’s perspective and its overall effects on their intention to leave in a startup company. To answer the research questions, the study employed an exploratory approach that utilizes qualitative method to collect primary data via face-to-face interviews. Data was collected from nine interviews from which all the participants are currently working in different startup companies. Because startup companies are very international and multicultural, the participants come from various backgrounds, work in different industries, and hold different positions in their current company. The collected data was then analyzed through content analysis approach. The results found that factors of job satisfaction such as work condition, interpersonal relationship, supervision, advancement, responsibility, and the work itself have a significant effect on employee satisfaction at work. Among the factors, supervision, work condition, and possibility for growth are those that concern the employees the most when it comes to turnover intention. The study also supports existing literature in which job satisfaction plays a vital role in keeping the employees happy, motivated, and willing to stay longer with the firm. In addition, the result suggests that job satisfaction and intention to leave can be varied from one to another based on an individual's needs and expectations. Therefore, managers in a startup should understand the employees’ ability, expectations and utilize the company's advantages in order to customize management strategies and retain their people.
Keywords: startup companies; work satisfaction; employees; labour turnover; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business